Some biomechanical features of medialization of the pressed and screwed-in cups in total hip arthroplasty in patients with dysplastic coxarthrosis - Loskutov, Oleg (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
After total joint replacement in patients with dysplastic coxarthrosis, a significant number of negative results are observed. One of the ways of solving the problem of primary stability of the endoprosthetic cup is its mediation by deepening the acetabulum in the zone of its a natomical center. Objective: top erform a comparative biomechanical evaluation of the stability of the cups that are fastened and screwed up, in the event of their mediation performed under the conditions of joint replacement in patients with dysplastic coxarthrosis. Methods: with the help of mathematical modeling, the relatively strong characteristics of the pelvic bone in the area of the acetabulum and the quality of fixation of cup and cup after their mediation and immersion in the zone of the anatomical center of the depression. The total displacement of the head of the femoral component of the implant is analyzed. Results: it was found that using scintillating cup under the condition of dysplastic coxarthrosis provides total displacement in (2.2 ÷ 2.4) times greater than in the situations of its application without defect of the acetabulum. When the cup is pressed, the total displacement is 4.7 times larger than the screw cup. In these cases, hip replacement with the use of pressed cups is accompanied by a high risk of their primary instability. Conclusions: the use of screw-in cups in the case of their mediation under the conditions of total joint replacement in patients with dysplastic coxarthrosis provides a more reliable primary stability than the ones pushed into cups. The level of tension in the pelvic bone of the acetabulum is influenced by the depth of the cup setting, with the increase of which there is a significant destruction of bone tissue. It is advisable to carry out the hip joint replacement in the case of dysplastic coxarthrosis using a screw-in cup.